Study of the effect of induced crystallization of lactose and manufacturing technology on the physicochemical, colorimetric, textural and rheological characteristics of dulce de leche - Gama Netto, Gabriel (2022)
Study of the Effect of Induced Crystallization of Lactose and Manufacturing Technology on the Physicochemical, Colorimetric, Textural and Rheological Characteristics of Dulce de Leche. Advisor: Ítalo Tuler Perrone. Co-advisors: Antônio Fernandes de Carvalho and Rodrigo Stephani. Dulce de leche (DL) is a very popular dairy product in Latin American countries and its production ranges from small artisanal producers using only two ingredients, milk and sucrose in a simple pan, to large dairy companies with different technologies and scale production. DL can be consumed directly or used in the preparation of dessert recipes. One of the great demands is the confectionery segment in which the DL is used as a topping and filling. For this type of application, the proper viscosity and consistency of the DL is important because it must remain structured in the confectionery products. The induced crystallization of lactose in DL is a common practice used by some dairy industries with the main objective of preventing the appearance of large lactose crystals that affect the sensory perception of the product in a defect known as sandiness. Larger dairy industries that have a vacuum concentration line for the manufacture of powdered milk and/or sweetened condensed milk use concentrated milk in the production of DL with the objective of reducing cost through energy savings. No studies were found in the literature that correlated the induced crystallization of lactose or a vacuum concentration step on the rheological properties of DL. Thus, this thesis was structured in two articles with the aim of evaluating the effect on DL properties caused by different manufacturing technologies commonly used by the dairy industry and using a standard DL recipe. The first article evaluated on a laboratory scale the effect of lactose induced crystallization under different conditions of temperature and stirring time on the physicochemical and colorimetric characteristics, texture profile and rheological behavior of DL. The second article evaluated in a pilot scale the effect of the manufacturing technology with different equipment and the induced crystallization of lactose on the physicochemical, colorimetric, texture profile and rheological behavior and sensory analysis of the DL. In both articles, the rheological behavior of the treatments was determined and adjusted to the mathematical model that best explains the flow profile in the flow curve analysis and the values of the storage modules (G') and loss (G") of energy were determined in oscillatory rheological analysis. Both the induced crystallization of lactose and the type of manufacturing technology were determinant in the properties of DL. Keywords: dulce de leche, lactose, crystallization, manufacturing technology.